Effect of emotional intelligence on problematic social media use among Chinese college students: mediating role of social exclusion and experiential avoidance - Hexu Guan; Sifan Peng; Zixin Liu; Huanran Sun; Hongxuan Wu; Xumei Yao; Zi Chen; Xi Yang (Frontiers in Psychiatry)
ObjectiveTo examine the mediating effects of social exclusion and experiential avoidance on college students’ emotional intelligence and problematic social media use.MethodsUsing convenience sampling, 1,448 students enrolled at nine public universities in Chengdu, Beijing, Shanghai, and Kunming were recruited from May 1, 2021, to October 28, 2021. The Emotional Intelligence Scale, the Social Exclusion Questionnaire for College Students, the Acceptance and Action Questionnaire, and the Problematic Mobile Social Media Use Assessment Questionnaire for Adolescents were used to conduct the survey.ResultsThe results showed that college students’ emotional intelligence was negatively correlated with social exclusion, experiential avoidance, and problematic social media use (p < 0.01). Social exclusion among college students was positively correlated with experiential avoidance and problematic social media use (p < 0.01), and experiential avoidance was positively correlated with problematic social media use (p < 0.01). This study revealed that college students’ emotional intelligence directly influences their problematic social media use. Social exclusion and experiential avoidance mediated, and sequentially chain-mediated, the effects of emotional intelligence on problematic social media use.ConclusionEmotional intelligence can potentially influence problematic social media use directly and indirectly through social exclusion and experiential avoidance.